ANALISIS NASKAH DRAMA LAKON YANG DITULIS KEMUDIAN KARYA BODE RISWANDI DENGAN MENGGUNAKAN PENDEKATAN STRUKTURALISME GENETIK : AN ANALYSIS OF THE PLAY SCRIPT YANG DITULIS KEMUDIAN BY BODE RISWANDI USING THE GENETIC STRUCTURALISM APPROACH - Nadya Dwi Yunita; Lala Nurnadila; Viona Sepahira; Adita Widara Putra (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to analyze the relationship between intrinsic and extrinsic elements by connecting the text structure with the social context and the author's worldview, so as to be able to understand the content of the work and the reasons behind its presentation. By understanding the text through the approach of genetic structuralism, we can understand more deeply how the intrinsic and extrinsic elements expressed by an author through the text or dialogue he creates. This research uses qualitative research methods that are carried out in order to build new knowledge through understanding and discovery. The results of this research are the main theme in the manuscript is resistance to oppression and dehumanization. There are nine characters with different characters, mixed plots, and diverse language styles. Settings include places, times, and events. The extrinsic element includes humanitarian and social facts that are reflected in the interaction between characters and indirect communication. The manuscript also features a collective subject, namely a society that lives in the shadow of a shattered memory. The author's worldview highlights the importance of women's role in building a civilized and sustainable society.